The Enhancement Reading Comprehension by Using Memes As Media In Teaching of The Second Year Students At SMP Negeri 7 Parepare - Hasriani Dewi; Ammang Latifa; Nasrullah (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2019)
This research was based on students' problems regarding English learning, especially the students' reading comprehension, where the students’ mean score was 53. The score was categorized low based on the assessment of the Dirjen Pendidikan Dasar dan Menengah 2016. Besides, this research was using memes to help the students’ reading comprehension. Memes are a combination of writing and images and expressions of people who function as entertainment and are spread by the internet. The purpose of this research is to find out whether or not the use of memes can enhance reading comprehension of the second year students at SMP Negeri 7 Parepare. Researchers applied pre-experimental design, with one groups of pre-test and post-test. The sample of the research consisted of 24 students from one class taken from the population of the second year student at SMP Negeri 7 Parepare l. this research consisted of three stages, namely the preparation stage, the implementation stage and the data analysis stage. The instrument was used in this research were the reading comprehension tests which aims to find out the extent of the students ability. The result of the data analysis showed that students' reading comprehension enhanced after giving treatment. It was showed by the mean score of the pre-test was 75.42 and the post-test was 84.04 the data shows that the reading comprehension of the second year students at SMP Negeri 7 Parepare enhanced by using memes. After analyzing the data by manually, the result of the t-test value (5.38) was higher than the t-table value (α = 0.05, out of 24 students = 2,069). The data indicated that H0 was rejected, H1 was accepted. In conclusion, teaching reading comprehension used meme was effective to enhance the reading comprehension of the second year students at SMP Negeri 7 Parepare of academic year 2018/2019.